2014
DOI: 10.1371/journal.pone.0098289
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in KERA Identified by Linkage Analysis and Targeted Resequencing in a Pedigree with Premature Atherosclerosis

Abstract: AimsGenetic factors explain a proportion of the inter-individual variation in the risk for atherosclerotic events, but the genetic basis of atherosclerosis and atherothrombosis in families with Mendelian forms of premature atherosclerosis is incompletely understood. We set out to unravel the molecular pathology in a large kindred with an autosomal dominant inherited form of premature atherosclerosis.Methods and ResultsParametric linkage analysis was performed in a pedigree comprising 4 generations, of which a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…So far, mutations in Low Density Lipoprotein receptor (LDLR), Low-Density Lipoprotein Receptor Related Protein 6 (LRP6) and Myocyte Enhancer Factor 2 A (MEF2A), Keratocan (KERA), Guanylyl Cyclase α1 subunit (GUCY1A3) and Chaperonin Containing TCP1, Subunit 7 (CCT7) have been published, although conflicting results have been reported for MEF2A. [7][8][9][10][11][12][13][14][15] Collectively, the identification of informative pedigrees with a dominant form of premature CVD have proven to be instrumental in the identification of novel variants in genes involved in the pathobiology of CVD, which may ultimately result in the new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…So far, mutations in Low Density Lipoprotein receptor (LDLR), Low-Density Lipoprotein Receptor Related Protein 6 (LRP6) and Myocyte Enhancer Factor 2 A (MEF2A), Keratocan (KERA), Guanylyl Cyclase α1 subunit (GUCY1A3) and Chaperonin Containing TCP1, Subunit 7 (CCT7) have been published, although conflicting results have been reported for MEF2A. [7][8][9][10][11][12][13][14][15] Collectively, the identification of informative pedigrees with a dominant form of premature CVD have proven to be instrumental in the identification of novel variants in genes involved in the pathobiology of CVD, which may ultimately result in the new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies, human genetics and animal studies support its role in the development of atherosclerosis [ 31 ]. Keratocan maintains the extracellular matrix, and rare genetic variants have been associated with premature atherosclerosis [ 32 ]. Among those present at lower concentrations in participants who died, transketolase may promote cardiomyocyte apoptosis and play a role in ischemic heart failure [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA extraction, whole exome sequencing and candidate variant selection were done as previously described [17]. Based on a PubMed search, variants were appointed as being athero-associated or not (Supplemental Table 1).…”
Section: Exome Sequencing and Mutation Analysismentioning
confidence: 99%
“…In these studies, 10% of the total CVD risk is attributed to common genetic variations, which suggests that low frequency variants are likely to play a role in the so-called 'missed heritability' [48,49]. Family studies have been proven to be extremely instrumental to investigate this and identified culprit genetic defects in families with extreme phenotypes [17,50,51]. Therefore, we have taken our pedigree as a model to study Netrin-1 in great detail.…”
Section: Limitationsmentioning
confidence: 99%